Peningkatan Motivasi Berprestasi dengan Gamifikasi pada Mata Pelajaran IPA Di SMPN 6 Siak Hulu Kabupaten Kampar Tahun Ajaran 2024\2025 - Wahyu Anggrayeni; Ibnu Hajar; Nurkhairo Hidayati (CV.ITTC INDONESIA, 2025)
The increasing use of games in learning shows significant potential to increase student motivation. This research aims to explore students' perceptions of the use of games in science learning on Ecology and Biodiversity material. The method used is a descriptive survey with a questionnaire distributed to junior high school students. The results show that the majority of students have a positive perception of the use of games in learning, especially in increasing motivation and understanding of the material. The use of games in science learning has the potential to increase student motivation, but care needs to be taken to ensure that game content remains relevant to the learning objectives.